Changes in plasma levels of BDNF and NGF reveal a gender-selective vulnerability to early adversity in rhesus macaques - Cirulli, Francesca (2008)
Early stressful events can increase vulnerability for psychopathology, although knowledge on the effectors is still limited. Here we tested the hypothesis that peripheral levels of Brain-Derived Neurotrophic Factor (BDNF) and Nerve Growth Factor (NGF), which are involved in the response to stress and in the pathophysiology of anxiety and depression, might be affected in a non-human primate model of adverse rearing. Males and females rhesus macaques reared with their mothers (MR) or in peer-only groups (PR) were used as experimental subjects. BDNF, NGF, adrenocorticotropic hormone (ACTH), cortisol and growth hormone (GH) were determined at baseline on postnatal days (PND) 14, 30 and 60 by means of specific ELISA and RIA procedures. In addition, behavior was assessed on PND 7, 14, 21, 30 (Brazelton test) and 60 (home cage observation). Data indicate gender differences in basal levels of BDNF throughout development. Peer-rearing increased significantly BDNF levels only in females. In addition, while all peer-reared subjects showed high levels of stereotypies and self-directed behaviors, behavioral passivity was selectively increased in females. By contrast, NGF levels were increased in response to peer rearing only in males, and correlated positively with other “classic” endocrine responses to stress, such as cortisol and growth hormone. Our data identify BDNF and NGF as neuroendocrine markers underlying differential responses to maternal deprivation in males and females rhesus macaques. The selective changes in BDNF levels in females could help explain the greater vulnerability to mood disorders of this gender reported in humans.